Effect of the venom of Bothrops diporus on the expression of Laminine 5 in equine foot biopsies - Teibler, Pamela (2018)
The aim of the present study was to study the expression of laminin 5 in equine foot biopsies precultured with venom of Bothrops diporus by histopathology and immunohistochemistry against untreated controls. The basal membranes of the laminae of the biopsies, as well as those of the interlamellar arterioles and veins, showed intense immunostaining of laminin 5 (L-5) in the control cultures; however, it was significantly lower in pre-cultured biopsies with the B. diporus venom concomitantly with the disruption of the typical laminar plate histoarchitecture. These results describe for the first time the normo-localization of L-5 in equine foot biopsies and the effect of the metalloproteinases, components of B. diporus venoms, both in the lamellar integrity and in the components of the vascularization.